STRATEGI PUSKESMAS TABANAN I DALAM PELAKSANAAN POSYANDU BALITA SEBAGAI UPAYA PEMANTAUAN STATUS GIZI BALITA PADA MASA PANDEMI COVID-19 - I Dewa Ayu Bintang Pradnya Dewi; Desak Putu Yuli Kurniati (Program Studi Sarjana Kesehatan Masyarakat Universitas Udayana Berasosiasi Dengan Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI), 2022)
Toddlers are vulnerable groups infected with COVID-19. Monitoring the nutritional status of toddlers through Posyandu Balita is very important to ensure the growth and development of toddlers is not disturbed. During the COVID-19 pandemic, monitoring the nutritional status of toddlers did not run optimally. This study aims to find out the strategy of Puskesmas Tabanan I in the implementation of Posyandu Balita as an effort to monitor the nutritional status of toddlers during the COVID-19 pandemic. The research design used is qualitative descriptive research. The research informant consisted of Tabanan I Puskesmas Officer, Village Midwife, Posyandu Cadre, Village Head and Toddler Mother. Data collection techniques with in-depth interviews and observations. This research was conducted during April to May 2021. Data analysis uses thematic analysis and data validation strategies using source triangulation, method triangulation and peer debriefing. The results showed that strategy of implementing Posyandu Balita was conducted with a home visit to monitor the growth of toddlers. Online media as a tools to dissemination of information about health of toddlers and the implementation of health protocols. Training to improve skills is needed in the development of the implementation strategy of Posyandu Balita during the COVID-19 pandemic. Keywords: Toodlers Posyandu, COVID-19, monitoring the nutritional status of toodlers, implementation strategies, Community Health Center